CONTRIBUTION OF THE ROLE OF INDONESIAN IMMIGRATION IN PREVENTING AND PROTECTING HUMAN RIGHTS AGAINST NON-PROCEDURAL MIGRANT WORKERS (PMI-NP) FROM TRANSNATIONAL CRIMES - Felix Ferdin Bakker; Tony Mirwanto (Polteknik Imigrasi, 2021)
Immigration is a law enforcement agency that functions as a public servant. Therefore, as an institution with authority to protect the traffic of people consisting of foreign nationals and Indonesian citizens, immigration policy has a crucial position in carrying out its duties and functions. However, the position of Immigration as a public servant with a human security aspect results in a consequence that must be taken, namely making a policy that balances service and in-depth supervision. Especially for Indonesian migrant workers who will work abroad. So Immigration is obliged to make various surveillance innovations as a contribution in terms of early detection both in terms of policies, regulations, technology, as well as improving the human resources of immigration officers in supervising migrant workers who are leaving, namely following procedures so that in the future it does not cause new problems in particular. Involved and entered into transnational crime both as victims and even perpetrators. This research is based on the writer's concern about the situation of PMI, considering that the migrant sector is one of the critical aspects in facilitating the country's development following the function of Immigration. This study uses a normative juridical method based on literature study materials and comparisons of policies taken with qualitative data. It is hoped that with this research, policy and technological innovation will contribute both legally and socially to the mitigation of the presence of undocumented migrant workers.